Development of contextual learning tools to support 21st century on flat shape materials - Nonong Rahimah; Dina Afriani (Math Didactic: Jurnal Pendidikan Matematika, 2021)
This study aims to develop and produce good quality learning tools on rectangular flat shape material and see the effectiveness of the learning. The population was the VII grade students at Junior High School in South Banjarmasin. Determination of the sample using purposive sampling with research samples SMPN 23 and 28 Banjarmasin. The research design used is a type of development research with a development process using the 4D model and has been adjusted to the research objectives. The results of the development of learning tools in the form of a Learning Implementation Plan (RPP), Student Worksheet (LKPD), and Learning Outcomes Test (THB) are good, namely valid with a little revision, THB meets the criteria of minimum validity is sufficient, the reliability test shows very high correlation practical, and effective seen from effective student activities, positive student responses, and completeness of learning classically achieved, namely 93.54% students complete learning for SMP 23 Banjarmasin and 93.33% students complete studying for SMPN 28 Banjarmasin. The urgency of the results of this study is to contribute to teachers at SMPN 23 and SMPN 28 Banjarmasin to be able to implement and develop the resulting products in the form of contextual-based learning tools. Since this product is a new thing for the schools of SMPN 23 and SMPN 28 Banjarmasin, it can be used as an alternative in learning activities.